Development of Students Worksheet Based STEM (Science, Technology, Engineering, and Mathematics) to Improve Student Critical Thinking Skill In Reaction Rate - Esty Ayu Fadhilatul Munawaroh; Bertha Yonata (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Development of Students Worksheet Based STEM (Science, Technology, Engineering, and Mathematics) to Improve Student Critical Thinking Skill In Reaction Rate. The aim of this study is to know the feasibility of students’ worksheets based on STEM to improve the ability of critical thinking on the reaction rate matter. The study uses a Research and Development (R D) design until the limited testing phase. The trial was conducted on 15 students in class XI MIA 6 Senior High School Hang Tuah 2 Sidoarjo. The instruments used are review and validation sheets, student response questionnaire sheets, knowledge, and critical thinking skills test sheets. The STEM-based Student Worksheets are feasible based on validity, practicality, and effectiveness aspect. Validity is reviewed based on content and construct with percentage each criterion are 81,25% (very valid) and 80,69% (valid). Practicality based on student responses shows of percentage 86,67% with very practice category. Effectivity based on results of knowledge and critical thinking skills tests with Wilcoxon test each show sig. (2-tailed) the score is 0,001 the meaning is before and after students have student worksheets is different, and the results of knowledge and critical thinking skills n-gain show 0,78 and 0,87 with high category. The n-gain results of critical thinking skills interpretation are 0,94, analysis is 0,76, and inferention is 0,86 with high category. So it can be concluded that STEM-based worksheets are feasible and can improve students' critical thinking skills.Keywords: Student Worksheets, STEM, Critical Thinking Skills, Reaction Rates DOI: 10.23960/jppk.v10.i3.2021.13